2023
DOI: 10.3390/ijerph20064745
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative HbA1c and Blood Glucose Measurements in Diabetes Mellitus before Oral Surgery and Implantology Treatments

Abstract: Diabetes mellitus has become a worldwide epidemic and is frequently accompanied by a number of complications proportional to the duration of hyperglycemia. The aim of this narrative review is to assess the most up-to-date guidelines on DM provided by both diabetes and dental associations. Furthermore, to gather evidence on the uni/bidirectional relationships of elevated HbA1c levels on dental surgery, implantology, bone augmentation, and periodontology and to demonstrate the importance of measuring HbA1c level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…In previous studies [15], HbA1c and blood glucose measurements have been stated to be a minimally invasive method to prevent diabetes complications. Additionally, diabetology and dentistry guidelines have reported that determining the relationship between HbA1c and glucose levels before implant treatment and oral surgery is an effective way to evaluate important complications [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies [15], HbA1c and blood glucose measurements have been stated to be a minimally invasive method to prevent diabetes complications. Additionally, diabetology and dentistry guidelines have reported that determining the relationship between HbA1c and glucose levels before implant treatment and oral surgery is an effective way to evaluate important complications [16].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, diabetology and dentistry guidelines have reported that determining the relationship between HbA1c and glucose levels before implant treatment and oral surgery is an effective way to evaluate important complications [16]. As a matter of fact, it has been reported that poorly controlled DM patients are an important risk factor for many dental surgeries and various dental complications may occur [15]. However, many studies have reported that the role of the relationship between HbA1c and glucose levels in the diagnosis of DM disease cannot be fully explained [17].…”
Section: Discussionmentioning
confidence: 99%